2019
DOI: 10.1016/j.jmbbm.2019.07.020
|View full text |Cite
|
Sign up to set email alerts
|

A review on the orthotics and prosthetics and the potential of kenaf composites as alternative materials for ankle-foot orthosis

Abstract: Since ancient Egypt, orthosis was generally made from wood and then later replaced with metal and leather which are either heavy, bulky, or thick decreasing comfort among the wearers. After the age of revolution, the manufacturing of products using plastics and carbon composites started to spread due to its low cost and form-fitting feature whereas carbon composite were due to its high strength/stiffness to weight ratio. Both plastic and carbon composite has been widely applied into medical devices such as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 40 publications
0
62
0
3
Order By: Relevance
“…The plant's core resembles wood and makes up 60-70% of the stem's dry weight; bark fibers contribute to the remaining 30-40%, and have a dense structure [9]. Several studies have reported the use of kenaf core fibers (KCF) as reinforcements in composite panels [10,11]. A study on KCF-reinforced unsaturated polyester composite revealed that 20 wt % of KCF reinforcements is the benchmark to enhance the composite's mechanical properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…The plant's core resembles wood and makes up 60-70% of the stem's dry weight; bark fibers contribute to the remaining 30-40%, and have a dense structure [9]. Several studies have reported the use of kenaf core fibers (KCF) as reinforcements in composite panels [10,11]. A study on KCF-reinforced unsaturated polyester composite revealed that 20 wt % of KCF reinforcements is the benchmark to enhance the composite's mechanical properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…Kenaf composite (Figure 5) is made of natural fibers with strong durability that meets the minimum criteria for mechanical properties required for AFOs [59]. Kenaf is a woody base plant that grows up to 5.5 m in 6-8 months; therefore, when used as a composite, its availability and production costs are not a problem [59,60].…”
Section: Kenaf Compositesmentioning
confidence: 99%
“…Kenaf composite (Figure 5) is made of natural fibers with strong durability that meets the minimum criteria for mechanical properties required for AFOs [59]. Kenaf is a woody base plant that grows up to 5.5 m in 6-8 months; therefore, when used as a composite, its availability and production costs are not a problem [59,60]. In addition, Kenaf fibers have a trait of absorbing oils and liquids, which can help reduce the possibility of skin irritation, as it can absorb sweat when used as an orthosis [59,61].…”
Section: Kenaf Compositesmentioning
confidence: 99%
“…The core fibers of kenaf (Hibiscus cannabinus), an annually grown crop in Malaysia, is a popular selection of reinforcements in composite panels. Incorporation of kenaf core fibers (KCF) has been reported to bestow the polymeric composites with better mechanical properties [12][13][14][15]. Nevertheless, the compatibility between hydrophobic polymers and hydrophilic natural fibers is an undesired problem that could affect the properties of the composite negatively, such as poor dimensional stability and poor durability against biological agents.…”
Section: Introductionmentioning
confidence: 99%